Family formation among adolescent Rohingya refugees; trajectories into adolescent marriage and childbearing in Cox’s Bazar Bangladesh - Linnea A. Zimmerman; Shatha Elnakib; Anam Ali; Rumana Akter; Tofajjel Hossain; Tom Traill; Kate Mieth; Tahia Hasan; Tanvir Hasan; W. Courtland Robinson (Conflict and Health)
Abstract Background Although both marriage and childbearing are potentially influenced by humanitarian emergencies, and for many individuals are intrinsically linked life-course events, they are rarely explored together in the literature on humanitarian emergencies. Additionally, literature on child marriage focuses largely on females, neglecting the experiences of males. Objective To understand how trajectories of family formation for adolescent females and males have been affected by mass displacement. We compare time to first marriage and time to first birth following marriage between age cohorts of 15–19 and 20–24 year-old female and male Forcibly Displaced Myanmar Nationals. Methods We use data from 1,565 females and 722 males aged 15–24, collected within fifteen camps in Cox’s Bazar, to estimate hazard of first marriage and of child marriage and data from 643 married females to estimate hazard from marriage to first birth. Results Females aged 20–24 had a 31% increased hazard of marriage overall and 42% increased hazard of child marriage relative to females aged 15–19 (95% CI: 1.07–1.87) and an 84% higher incidence rate (95% CI: 1.46–2.33). For males, there was a higher hazard of marriage by age 25 amongst males aged 20–24 relative to age 15–19 (HR: 1.80, 95% CI: 1.10–2.94), but no statistically significant difference in the hazard of marriage by age 18. Approximately 20% of females gave birth within a year of marriage and 70–75% within three years post-marriage, across age cohort and age at marriage. There were no statistically significant differences in hazard of first birth by either age cohort or age at marriage. Discussion Displacement may have increased risk of child marriage for adolescents, as evidenced by higher child marriage rates amongst males and females who were age 14–18 at the time of displacement. Displacement did not affect time to childbirth following marriage, which remains high amongst both age cohorts. Efforts to reduce child marriage and adolescent child marriage must address limited opportunities for adolescents in situations of displacement. Clinical trial number Not applicable.